Morphological training in spelling: Immediate and long-term effects of an interventional study in French third graders. (February 2018) - Casalis, Séverine; Pacton, Sébastien; Lefevre, Françoise; Fayol, Michel
Highlights: We conducted an interventional study based on morphology to improve spelling in third graders. Morphological training was more effective than typical classroom spelling activities. The impact of the training had a direct impact on derived word spelling accuracy. The benefit of the intervention persists over time and was still visible five months after the end of the training.